AB0487 TAKAYASU'S ARTERITIS: RECOGNIZING AN OLD ENEMY. (13th June 2020) - Torres, F.; Jaramillo Arroyave, D.; Muñoz, C.; Hernandez, L.; Vásquez, G.; Restrepo Escobar, M.; González, L. A.; Vanegas, A.
Abstract : Background: Takayasu's arteritis (AT) is a systemic vasculitis that affects large vessels, mainly the aorta, its branches and the pulmonary arteries. There are few data on their behavior in our region. Objectives: to describe the clinical and angiographic characteristics and outcomes of a group of patients with AT. Methods: a cross-sectional, retrospective study based on a secondary source taken from two high complexity hospitals in Medellin - Colombia between August 2011 and December 2018. Results: medical records of 41 patients were evaluated, 87.5% met the 1990 ACR criteria of AT. The majority were women (95.1%), with a median age at the time of diagnosis of 22 years (IR 52), 11 patients (26.8%) were over 40 years old at debut. The median delay in diagnosis was 12 months (IR: 167). Systemic symptoms included general malaise (29.3%), weight loss (29.3%) and fever (19.5%); the main vascular manifestations were hypertension and blood pressure difference (61%), headache (39%), upper limb claudication (31.7%), dyspnea (29.3%), angina (26.8%) and carotidinia (22%). Most frequent findings on physical examination were pulse absence or decrease (78%) and subclavian murmur (53.7%). ESR and CRP were found high in 85.3% and 22%, respectively. Angiographic studies revealed stenosis or occlusion in multiple arterial territories, being the stenosis of the left subclavian artery the most frequent lesion (68.3%), followed by the involvement of the abdominal aorta (58.5%) and thoracic (51%). The distribution according to Hata-Numano classification was: type V (58.5%), type I (17.1%) and type IIa (7.3%), indicating complex vascular lesions and associated serious complications. Abnormalities of the renal arteries, pulmonary arteries involvement, and aortic insufficiency were present in 39%, 14.6%, and 7.3% respectively. Seventy-five percent of patients had active disease, glucocorticoids were the main treatment in 90.2% of the cases, used isolated (2.4%) or in combination with other immunosuppressants (87.8%), including methotrexate (75.6%), azathioprine (26.8%) and cyclophosphamide (14.6%); vascular interventions were performed in 11 patients (26.8%). Most relevant vascular complications were renovascular hypertension (26.8%), stroke (19.5%), chronic kidney disease (19.5%) and chronic heart failure (17.1%). From the clinical point of view, our findings were similar to those shown in series from Brazil, Japan, and Turkey. Contrary to what was reported in other series, carotidinia was a finding that occurred in almost a quarter of our patients (23%) and maybe one of the initial symptoms of the disease. The findings of the vascular physical examination are similar to those reported by the IRAVAS group, where the asymmetry of the pulses was most frequent, followed by the presence of murmurs and the difference in blood pressure, claudication being less frequent in the upper and lower limbs. Conclusion: patients in this series are characterized by having an extensive disease partly due to a late diagnosis, with a high percentage of complications associated with vascular stenotic compromise, which generates morbidity and impact on the quality of life. References: [1]Sato EI, et al. Takayasu arteritis. Treatment and prognosis in a university center in Brazil, Int J Cardiol. 2000; 75 Suppl 1: S163-6. [2]Arnaud L, et al. Takayasu arteritis in France: a single-center retrospective study of 82 cases comparing white, North African, and black patients. Medicine (Baltimore). 2010; 89(1): 1-17. Disclosure of Interests: None declared